Usuń nawiasy i wykonaj redukcję wyrazów podobnych
a) (2x²+4x-3)-(-x²-2x+4)
b) (3/5m²+2/3n²+6)+(-1/3m²-2/3n²-2 3/5) ten zapis np.3/5 ułamek
c)(0,5xy²-1,2y²+5)+(-0,8y²-2,5xy²-2 1/8)
Wykonaj odejmowanie
a (6a²+2a+z)-(-3a²-2a+5)
b (12 ½m²-1¼n²-1,6)-(2¼m²+3¾n²+2,4)
c (1,5x²y-¾x²-15)-(⅖x²y-2 2/3-1/8x²)

2

Odpowiedzi

2010-02-28T13:12:04+01:00
2010-02-28T13:33:28+01:00
A) (2x²+4x-3)-(-x²-2x+4)=2x²+4x-3+x²+2x-4=3x²+6x-7
b)(⅗m²+⅔n²+6)+(-⅓m²-⅔n²-2⅗)=⅗m²+⅔n²+6-⅓m²-⅔n²-2⅗=⅖m²+3⅖
c)(0,5xy²-1,2y²+5)+(-0,8y²-2,5xy²-2⅛)=0,5xy²-1,2y²+5-0,8y²-2,5xy²-2⅛=-2xy²-2y²+2⅞
a)(6a²+2a+z)-(-3a²-2a+5)= 6a²+2a+z+3a²+2a-5= 9a²+2a-5+z
b)(12½m²-1¼n²-1,6)-(2¼m²+¾n²+2,4)=12½m²-1¼n²-1,6-2¼m²-¾n²-2,4=10¼m²-2n²-4
c)(1,5x²y-¾x²-15)-(⅖x²y-2⅔-⅛x²)=¾x²y-⅝x²-12⅓